Anais Do X Congresso Brasileiro De Engenharia Química 2014
DOI: 10.5151/chemeng-cobec-ic-07-eb-116
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DA INFLUÊNCIA DO FÓSFORO NA BIOACUMULAÇÃO DO CHUMBO PELA Eichhornia crassipes

Abstract: RESUMO -O objetivo deste trabalho foi avaliar a influência do macronutriente fósforo no processo bioacumulação de chumbo, usando a macrófita aquática Eichhornia crassipes. Preparou-se diversas soluções de cultivo baseado no conjunto de macro e micronutrientes especificado na solução hidropônica de Clark, contendo ainda chumbo (0, 5, 10, 15 e 20 mg L -1 ) e fósforo (uma, duas, quatro e oito vezes 3,2 mg L -1 ) em diferentes concentrações. Em estufa, aproximadamente 80 g da E. crassipes viva e saudável, foram cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
3
0
3
Order By: Relevance
“…Differing results were presented by Mangabeira et al (2004), who identified the presence of deposits in apoplastic areas through histological cuts, indicating the occurrence of cadmium translocation to other compartments of the plant despite the greatest accumulation of the metal occurring in the roots. The translocation of lead (Oliveira, 2012) and glyphosate (Martins et al, 2009) into tissues of E. crassipes is still reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Differing results were presented by Mangabeira et al (2004), who identified the presence of deposits in apoplastic areas through histological cuts, indicating the occurrence of cadmium translocation to other compartments of the plant despite the greatest accumulation of the metal occurring in the roots. The translocation of lead (Oliveira, 2012) and glyphosate (Martins et al, 2009) into tissues of E. crassipes is still reported.…”
Section: Resultsmentioning
confidence: 99%
“…The recommended pH of culture water for plant growth is between 6 and 8, with temperature between 25°C and 28°C, although the species can survive over a wide temperature range (e.g. Oliveira, 2012). This macrophyte is distributed in practically all water bodies in Brazil, with yield values of up to 1,000 kg.ha -1 .d -1 (Costa, et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Já o enxofre (S) é um macronutriente presente em proteínas, aminoácidos, vitaminas, coenzimas e outros complexos orgânicos, com importância fundamental na síntese de clorofila (Romeiro, 2012). Segundo Oliveira (2012) A água residuária utilizada foi coletada na granja de suinocultura do próprio Instituto e devidamente transportada em recipientes de 100 L para o local de execução do experimento, onde foi submetida ao processo de filtragem, através de um filtro constituído com várias camadas de areia e brita e também ao processo de desinfeção solar (SODIS: solar desinfection).…”
Section: Introductionunclassified
“…In fact, several research works have been performed on plant species used as possible lead phytoremediation, such as: Pistia stratiotes (OLIVEIRA, 2010), Leucaena leucocephala (BOURLEGAT et al, 2008), Eichhornia crassipes (PEREIRA, 2010;OLIVEIRA et al, 2014), Stizolobium aterrimum , Pluchea sagittalis (ROSSATO, 2010), Ricinus communis (LIMA, 2010b), Helianthus annuus (LIMA, 2010), Canavalia ensiformis (ROMEIRO et al, 2007), Mucuna aterrima (SANTOS et al, 2012), Jatropha curcas (GOUVEIA et al, 2015), Salvinia auriculata (ALMEIDA, 2014). (PEREIRA, 2010), and the metal accumulation in the aerial part of the plant .…”
Section: Lead Remediation In the Environmentmentioning
confidence: 99%